Respuesta :
Answer:
[tex]y = \dfrac{-1}{4}x + \dfrac{-27}{4}[/tex]
Step-by-step explanation:
The equation of a line is:
y = mx + b
Where:
m = slope
b = y-intercept
First thing we need to do is solve for the slope. The slope formula is:
[tex]m = \dfrac{y_2-y_1}{x_2-x_1}[/tex]
Where:
x₁ = x-coordinate of the first point
x₂ = x-coordinate of the second point
y₁ = y-coordinate of the first point
y₂ = y-coordinate of the second point
We are given the following points:
Point 1: (-3, -6)
Point 2: (5, -8)
So let's plug in our coordinates into the slope formula:
[tex]m = \dfrac{y_2-y_1}{x_2-x_1}\\\\ =\dfrac{(-8)-(-6)}{5-(-3)}\\\\ =\dfrac{-2}{8}\\\\ =\dfrac{-1}{4}[/tex]
So we have our new equation of this line:
[tex]y = \dfrac{-1}{4}x + b[/tex]
What do we do then about the y-intercept?
Our points will help us out by plugging them in our equation, so we can solve for our y-intercept (b).
Let's do both to show that it would be the same:
Point 1 (-3, -6)
[tex]y = \dfrac{-1}{4}x + b\\\\-6 = \dfrac{-1}{4}(-3) + b\\\\-6 = \dfrac{3}{4} + b\\\\-6 = \dfrac{3}{4} + b\\\\subtract \dfrac{3}{4}\;from\;both\;sides\;of\;the\;equation\\\\-6- \dfrac{3}{4}= \dfrac{3}{4}- \dfrac{3}{4}+b\\\\\\\dfrac{-24-3}{4}=0+b\\\\\\-\dfrac{27}{4} = b[/tex]
Point 2: (5, -8)
[tex]y = \dfrac{-1}{4}x + b\\\\-8 = \dfrac{-1}{4}(5) + b\\\\-8 = \dfrac{-5}{4} + b\\\\-8 = \dfrac{-5}{4} + b\\\\subtract \dfrac{-5}{4}\;from\;both\;sides\;of\;the\;equation\\\\-8- \dfrac{-5}{4}= \dfrac{-5}{4}- \dfrac{-5}{4}+b\\\\\\\dfrac{-32-(-5)}{4}=0+b\\\\\\\dfrac{-27}{4} = b[/tex]
Now that we have b, we can insert that into the equation of the line:
[tex]y = \dfrac{-1}{4}x + b\\\\y = \dfrac{-1}{4}x + \dfrac{-27}{4}[/tex]